2013
DOI: 10.1016/j.dr.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Whom do children copy? Model-based biases in social learning

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Developmental Review. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reected in this document. Changes may have been made to this work since it was submitted for publication. A denitive version was subsequently published in Developmental Review, 33, 4, December 2013, 10.1016/j.dr.20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(141 citation statements)
references
References 110 publications
3
125
0
3
Order By: Relevance
“…Indeed, in our rice carrying task, all first-generation children copied the adult's use of the most inefficient tool, the small piece of cardboard, when it was demonstrated pedagogically. It was only once children were observing peers, rather than adults, performing the task that the inefficient tool choices started to drop out -in line with other studies showing that children usually copy adults more closely than peers (for a review see Wood, Kendal, & Flynn, 2013). Thus children's well-documented tendency to overimitate might compete with their tendency to innovate at this age.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, in our rice carrying task, all first-generation children copied the adult's use of the most inefficient tool, the small piece of cardboard, when it was demonstrated pedagogically. It was only once children were observing peers, rather than adults, performing the task that the inefficient tool choices started to drop out -in line with other studies showing that children usually copy adults more closely than peers (for a review see Wood, Kendal, & Flynn, 2013). Thus children's well-documented tendency to overimitate might compete with their tendency to innovate at this age.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, a previous study of the same population found a tendency for sons of mothers who more frequently associated with adult males during their immaturity to achieve higher rank as adults (37). Theory and empirical research predict that individuals will exhibit biases in which models they choose to observe to avoid unreliable information and maximize the transfer of useful information (56)(57)(58). Importantly, there is evidence that young male chimpanzees attend to same-sex models and sex-typical behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Another 656 explanation of this first-touch divergence is that capuchins had less understanding of the taskmaterial than the children and tried to access the reward through the transparent plastic. conservatism in the no-demonstration conditions is surprising given that previous work with 673 five-year-olds has shown that personal exploration may encourage multiple-method adoption 674 (Wood, Flynn, & Kendal, 2013). An age difference may explain these differences.…”
Section: Divergent Behavioral Patterns 598mentioning
confidence: 91%